Autophagy Induced by the N-Terminus of the Classic Swine Fever Virus Nonstructural Protein 5A Protein Promotes Viral Replication - Zhang, Chengcheng; Wang, Xiuling; Sun, Jiahao; Guo, Mengjiao; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2021)
Although classical swine fever virus (CSFV) infection has been reported to induce autophagy, the specific induced mechanism remains unrevealed. Nonstructural protein 5A (NS5A) of CSFV is a multiphosphorylated protein with multiple functions to regulate viral replication and the host cell immune responses. Herein, we demonstrated that CSFV NS5A could induce cellular autophagy and promote viral replication. In the current study, we showed that NS5A expression significantly increased the levels of autophagy-related genes, including LC3, ATG5, and Beclin 1; conversely, degradation of P62/SQSTM1 was observed by Western blotting. The number of autophagy-like vesicles was also obviously increased in NS5A-expressing cells, as analyzed by transmission electron microscopy. Furthermore, we observed the co-localization of the NS5A and LC3 proteins by confocal immunofluorescence analysis. Direct binding of NS5A to the autophagy-related LC3 protein was confirmed by coimmunoprecipitation in vivo and by a GST pulldown assay in vitro. Through segmentation and point mutation research on the NS5A protein, we found that the N-terminal region and the phosphorylation of amino acids 81 and 92 of the NS5A protein were essential for inducing autophagy. Finally, we demonstrated that the LC3 protein had a positive effect on CSFV replication. These findings emphasize a previously unascertained interaction relationship between NS5A and LC3 in the autophagy process. Furthermore, our research revealed a new role of CSFV NS5A, particularly its N-terminal amino acids serine 81 and serine 92, as a critical regulator of CSFV-induced autophagy and have significance for extending our understanding of the CSFV-autophagy interplay.